PENGEMBANGAN BAHAN AJAR KURIKULUM PEMBELAJARAN UNTUK PENDIDIKAN GURU SEKOLAH DASAR - isnaini wulandari; Ndaru Mukti Oktaviani (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aims to: 1) develop appropriate learning materials for the subject learning curriculum for students at PGSD Kuningan University and 2) determine the effectiveness of learning materials for the subject learning curriculum for students at PGSD Kuningan University. This type of research is research and development (R&D). This research development stage refers to the Borg and Gall development model which has been grouped into three groups, namely: 1) preliminary study, 2) development and 3) testing and implementation. Preliminary test subjects are two expert validators. The main test subjects were students of PGSD Universitas Kuningan Semester V. The instrument of data collection used a material expert assessment sheet, a student response questionnaire sheet on the product. The data analysis technique of the validator's assessment results in the limited test used Aiken's V. The data analysis technique used scoring. The results of this study are as follows: 1) the results of the assessment of learning materials for the subject learning curriculum average score of Aiken's V is 0.918 because the range of V numbers is between 0 to 1.00, the product developed is categorized very feasibly. 2) The average percentage of each indicator in the questionnaire is 86.89%. This figure can be interpreted that the product of learning materials for the subject learning curriculumthat has been made is very effective because it is in the range of 81%-100%.